Mass Customization in the House Building Industry: Literature Review and Research Directions - Larsen, Maria Stoettrup Schioenning; Lindhard, Søren Munch; Brunoe, Thomas Ditlev; Nielsen, Kjeld; Larsen, Jesper Kranker (Frontiers in Built Environment, 2019)
Mass Customization is a manufacturing paradigm which enables customized and personalized design at a cost near mass production. Mass Customization’s ability to lower unit cost, increase quality, and shorten project duration for customized offerings is considered highly relevant for tomorrow’s house building industry. Therefore, through a literature review this research investigates state-of-the-art in Mass Customization in the house building industry from four perspectives: 1) Mass Customization in the house building industry, 2) modular and off-site construction, 3) construction supply chains, and 4) customer satisfaction. It is concluded that a great potential exists for applying Mass Customization in the house building industry. However, despite its potential, research on Mass Customization in the house building industry is sparse. In particular research on developing the solution space and choice navigation tools is limited in this industry.